2017
DOI: 10.1609/icwsm.v11i1.14883
|View full text |Cite
|
Sign up to set email alerts
|

The Substantial Interdependence of Wikipedia and Google: A Case Study on the Relationship Between Peer Production Communities and Information Technologies

Abstract: While Wikipedia is a subject of great interest in the computing literature, very little work has considered Wikipedia’s important relationships with other information technologies like search engines. In this paper, we report the results of two deception studies whose goal was to better understand the critical relationship between Wikipedia and Google. These studies silently removed Wikipedia content from Google search results and examined the effect of doing so on participants’ interactions with both websites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…However, very recent work has suggested that search engines, despite their power and profitability, may be surprisingly dependent on a resource that is both volunteercreated and freely available: user-generated content (UGC), and specifically Wikipedia. In particular, McMahon et al (2017) found that search engine result page (SERP) click-through rates dropped drastically from 26% to 14% when Wikipedia results were removed from SERPs. This drop in click-through ratea critical search engine evaluation metricis enough to easily wipe out gains made by even major improvements to search engine algorithms, for instance the introduction of deep learning (Clark 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, very recent work has suggested that search engines, despite their power and profitability, may be surprisingly dependent on a resource that is both volunteercreated and freely available: user-generated content (UGC), and specifically Wikipedia. In particular, McMahon et al (2017) found that search engine result page (SERP) click-through rates dropped drastically from 26% to 14% when Wikipedia results were removed from SERPs. This drop in click-through ratea critical search engine evaluation metricis enough to easily wipe out gains made by even major improvements to search engine algorithms, for instance the introduction of deep learning (Clark 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Google committed to transferring all content from Freebase, a Google-owned knowledge graph, to Wikidata (Pellissier Tanon et al 2016), indicating their intention to continue relying on Wikidata to help populate Google Search results. However, Google does little to support Wikidata other than exploit the knowledge it contains, and may even reduce traffic to Wikidata by displaying knowledge in its own search panels without crediting Wikidata (McMahon, Johnson, and Hecht 2017).…”
Section: Wikidata As Social Mediamentioning
confidence: 99%
“…This further validates our shock identification procedure. Indeed, Wikipedia and search engines (such as Google) play an important role in each other's traffic and quality (McMahon, Johnson, and Hecht 2017).…”
Section: Change In Collaboration Dynamics With Shocksmentioning
confidence: 99%